Uropathogens and their antibiotic sensitivity pattern among poorly controlled diabetic Pakistani patients with Asymptomatic Bacteriuria - Sheikh, Nadeem Islam; Zahoor, Ambreen; Naseem, Sajid; Yasir, Ali (International Journal of Endorsing Health Science Research, 2018)
Background: Urinary tract infections (UTIs) are common among diabetic patients, 60% of the patients with diabetes mellitus (DM) have risk of UTI and two third of them develop symptomatic or asymptomatic UTIs. The uropathogens may vary in their susceptibility to antimicrobials from place to place and time to time, therefore susceptibility pattern of predominant organisms against antimicrobials is essential. The aim of the study was to investigate the incidence of asymptomatic bacteriuria (ASB) and UTIs in clinically diagnosed diabetic patients and to determine the uropathogens responsible for ASB and UTIs as well as their antimicrobial susceptibility pattern. Methodology: An observational, prospective study was conducted at the Islamabad Social Security Hospital, Pakistan. Total 269 patients were recruited as per the study inclusion/exclusion criteria. Fasting blood glucose (FBG), blood sedimentation rate (BSR), urine routine examination (RE), abdominal ultrasound and hemoglobin-A1c (HbA1c) were examined in all patients to exclude other causes of urosepsis. Results: According to the study results 106 urine cultures were positive in the absence of urinary symptoms. Majority of the study subjects were around 50 years of age with an average glycosylated hemoglobin level of 8.98 g/dl. Urine culture and sensitivity test showed that E coli - Extended-spectrum beta-lactamases (ESBL) isolated in 39.63% was the most common organism sensitive to Tazobactam and Tiegecycline. E coli isolated in 32% was observed sensitive to levofloxacin, cefotaxime and tazobactam. Klebsiella (ESBL) isolated in 5.6% and found sensitive to tazobactum and amikacin. Klebsiella saprophyticus isolated in 3.77% with greater sensitivity to Tazobactum and cefixime while Enterococcus isolated in 5.6% mainly sensitive to minocycline and vancomycin. Majority of the isolated organisms were poorly sensitive or resistant to cefixime, quinolones and amoxiclav. Conclusion: Asymptomatic bactriuria is common in type 2 diabetic patients. The growth and sensitivity of microorganism reveal resistance and poor sensitivity to commonly used oral antibiotics therefore it is mandatory to treat UTI only after isolation of microorganisms according to culture and sensitivity to prevent resistant strains.